Beta-Blockers for the Treatment of Essential Hypertension: What are the Arguments Against Their Use as First Line Therapy? - Burnier, Michel; Bullani, Roberto; Vogt, Bruno (Current Hypertension Reviews, 2007)
Beta-blockers are recommended as first line therapy in the treatment of essential hypertension since several decades and this recommendation has been endorsed by most if not all national and international guideline committees. Some concerns about their efficacy in elderly hypertensive patients have been raised in the mid-90ies. With the recent publication of the LIFE and ASCOT-BPLA trials showing the superiority of a losartan-based and an amlodipine-based regimen versus an atenolol-based regimen in preventing stroke, additional questions have been raised about the position of beta-blockers in the management of hypertensive patients. Conventional beta-blockers such as atenolol have a well known negative impact on metabolic parameters which may limit their efficacy in protecting patients from the development of cardiovascular events. More recent data have also suggested that atenolol leads to lesser decrease in central blood pressures than amlodipine and this may explain why atenolol does not provide as much protection against stroke than calcium antagonists and angiotensin receptor blockers. With these new evidence, it appears legitimate to call in question the place of beta-blockers as first choice therapy in essential hypertension.
Keywords: Beta-blockers